Metabolic voxel‐based analysis of the complete human brain using fast 3D‐MRSI: Proof of concept in multiple sclerosis. Issue 2 (12th January 2016) - Donadieu, Maxime; Le Fur, Yann; Lecocq, Angèle; Maudsley, Andrew A.; Gherib, Soraya; Soulier, Elisabeth; Confort‐Gouny, Sylviane; Pariollaud, Fanelly; Ranjeva, Marie‐Pierre; Pelletier, Jean; Guye, Maxime; Zaaraoui, Wafaa; et al.
Abstract : Purpose: To detect local metabolic abnormalities over the complete human brain in multiple sclerosis (MS) patients, we used optimized fast volumic echo planar spectroscopic imaging (3D‐EPSI). Materials and Methods: Weighted mean combination of two 3D‐EPSI covering the whole brain acquired at 3T in AC‐PC and AC‐PC+15° axial planes was performed to obtain high‐quality metabolite maps for five metabolites: N‐acetyl aspartate (NAA), glutamate+glutamine (Glx), choline (Cho), myo‐inositol (m‐Ins), and creatine+phosphocreatine (tCr). After spatial normalization, maps from 19 patients suffering from relapsing‐remitting MS were compared to 19 matched controls using statistical mapping analyses to determine the topography of metabolic abnormalities. Probabilistic white matter (WM) T 2 lesion maps and gray matter (GM) atrophy maps were also generated. Results: Two‐group analysis of variance (ANOVA) (SPM8, P  < 0.005, false discovery rate [FDR]‐corrected P  < 0.05 at the cluster level with age and sex as confounding covariates) comparing patients and controls matched for age and sex showed clusters of abnormal metabolite levels with 1) decreased NAA (around –15%) and Glx (around 20%) predominantly in GM within prefrontal cortices, motor cortices, bilateral thalami, and mesial temporal cortices in line with neuronal/neuro‐astrocytic dysfunction; 2) increased m‐Ins (around + 20%) inside WM T 2 lesions and in the normal‐appearing WM of temporal‐occipital lobes, suggesting glial activation. Conclusion: We demonstrate the ability to noninvasively map over the complete brain—from vertex to cerebellum—with a validated sequence, the metabolic abnormalities associated with MS, for characterizing the topography of pathological processes affecting widespread areas of WM and GM and its functional impact. J. Magn. Reson. Imaging 2016;44:411–419.